Knowledge Sharing among Employees in Organizations - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2019)
Knowledge is considered as the basis for developing sustained long-term competitive advantage for every organization. In the 21st century every organization becomes knowledge based for the sustainable development. Knowledge sharing is an important instrument that turns individual knowledge into group organizational knowledge. It is one of the main knowledge processes in a present dynamic and competitive era for the development of organizations. The knowledge sharing practice plays a remarkable role in the development and innovation in many areas of organizations. In this paper an attempt has been taken to discuss techniques, barriers and benefits of knowledge sharing in organizations.